Identification and Characterization of Arthrobacter nicotinovorans JI39, a Novel Plant Growth-Promoting Rhizobacteria Strain From Panax ginseng - Jiang, Yun; Song, Yu; Jiang, Chengyang; Li, Xiang; Liu, Tingting; Wang, Jiarui; Chen, Changqing; Gao, Jie (Frontiers in Plant Science, 2022)
A bacterial strain JI39 that had plant growth-promoting traits was isolated from the rhizosphere soil of Panax ginseng. It had the ability to produce high indole-3-acetic acid (13.1 μg/ml), phosphate solubilization (164.2 μg/ml), potassium solubilization (16.1 μg/ml), and nitrogen fixation. The strain JI39 was identified to be Arthrobacter nicotinovorans based on morphological, physiological, and biochemical traits and through 16S rDNA sequence analysis. The optimal culture environment for strain growth was 1.0% NaCl, 30°C, pH 6.0, and without UV irradiation. The strain can produce cellulase and protease. The strain JI39 can significantly promote the growth of ginseng. After ginseng seeds were treated with 3 × 108 CFU/ml of JI39 bacterial suspension, the shoot's length was significantly increased by 64.61% after 15 days. Meanwhile, the fresh weight of 2-year-old ginseng roots was significantly increased by 24.70% with a treatment by the 108 CFU/ml bacterial suspension after 150 days in the field. The gene expression of phenylalanine ammonia-lyase (PAL), β-1.3 glucanase (β-1,3-GA), chitinase (CHI), superoxide dismutase (SOD), and peroxidase (POD) of ginseng was upregulated, and it also can improve the soil urease, phosphatase, invertase, and catalase activity. In conclusion, the bacterial strain JI39 could efficiently promote the growth of ginseng and has the potential to be a good microbial fertilizer for ginseng.